Implementasi Penegakan Hukum Disiplin bagi Anggota Polri sebagai Perwujudan Birokrasi Good Governance dan Clean Government - Hermansyah, Eko; Toroby, Renida Jozelina; Rahardjo, Djoko (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the Implementation of disciplinary law enforcement for members of the Indonesian National Police as a manifestation of good governance and clean governance bureaucracy. The study uses a qualitative and descriptive methodology. The data collection technique used by researchers in this study was through interviews. Data analysis techniques start with coding, word frequency, hierarchy chart, coding diagram, coding comparison diagram, data display, conclusion drawing, and source triangulation with the help of N-FIVO software. The results of the study indicate that the Implementation of disciplinary law enforcement for members of the Indonesian National Police as a manifestation of good governance and clean governance bureaucracy consists of upholding member discipline, responsibility for duties, obeying the law, exemplary leaders, community service, and preventing extortion. Keywords: Clean Governance, Good Governance, Implementation, Law Enforcement, Indonesian National Police.